Membangun Lulusan Siap Masa Depan: Inisiatif Strategis Pesantren dalam Mempersiapkan Santri Untuk Revolusi Industri 4.0 - Wakhid, N.S Lubbi Abdur rahman (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
The rapid advancement of technology requires Islamic boarding schools (pesantren) to adapt in order to remain relevant in the digital era. This study aims to identify the strategic steps taken by Pondok Pesantren Wahid Hasyim, particularly in the Ahmad Syafi’i Complex, in responding to technological changes and the challenges of the Fourth Industrial Revolution. The research employs a descriptive qualitative approach, with data collected through interviews with the head of the complex and the curriculum coordinator of SMK Ahmad Syafi’i Academy, as well as documentation in the form of observations, photos, and institutional records. The findings reveal four main strategies implemented: (1) establishing SMK Ahmad Syafi’i Academy to provide vocational education and training, (2) launching an entrepreneurship program to foster an entrepreneurial mindset among the students, (3) developing a programming boot camp to enhance students' digital skills, and (4) offering Arabic and English language courses to strengthen global communication skills. These strategies aim to equip students with the skills necessary to compete in the digital era while maintaining core Islamic educational values. This study provides valuable insights into strategic innovations that integrate tradition with modernity, offering lessons for other Islamic educational institutions facing similar challenges.